1998
DOI: 10.1080/0952398980350204
|View full text |Cite
|
Sign up to set email alerts
|

A General Framework for the Development of Web‐Based Instruction

Abstract: Based on a significant need for categorizing the various components available for use in Web-based instruction, the authors have developed a hierarchical framework for describing the instructional activities common with this form of instruction. This framework includes six levels ranging from simple information delivery to immersive collaborative environments and includes the general instructional perspective, Web/Internet activities, and specific examples of Web-based components and tools for each level. It i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…They have also revealed that expert instructional designers rely on casespecific strategies in guiding the design process. Still, researchers such as Atchison (1996) and Rowland (1992a, b) have raised concerns about the lack of systematic investigation of the gap between the actual instructional design process practiced by experts and so-called instructional design models, urging the need for further developing understanding and methods of capturing the quintessence of expert practice. They have argued that a significant portion of the instructional design process varies from the commonly held, ''rational'' (or procedural) view of instructional design and represents a reflective and creative process based on observations of the iterative, cyclical, and ad hoc design processes used in practice.…”
Section: Research On Expertise In Instructional Designmentioning
confidence: 99%
See 2 more Smart Citations
“…They have also revealed that expert instructional designers rely on casespecific strategies in guiding the design process. Still, researchers such as Atchison (1996) and Rowland (1992a, b) have raised concerns about the lack of systematic investigation of the gap between the actual instructional design process practiced by experts and so-called instructional design models, urging the need for further developing understanding and methods of capturing the quintessence of expert practice. They have argued that a significant portion of the instructional design process varies from the commonly held, ''rational'' (or procedural) view of instructional design and represents a reflective and creative process based on observations of the iterative, cyclical, and ad hoc design processes used in practice.…”
Section: Research On Expertise In Instructional Designmentioning
confidence: 99%
“…Although there have been several research studies attempting to systematically investigate expert performance in instructional design (Rowland 1992a, b;Atchison 1996;Le Maistre 1998), few of them provided details and guidance concerning the selection of experts.…”
Section: Selection Of Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The World Wide Web (web) has been used for many purposes including information delivery with pre-defined resources, information delivery with online interaction, pre-designed instructional delivery, information synthesis, creation of resources and immersive collaborative environments (Bannan-Ritland, Harvey & Milheim, 1998;Flake, 2001;Herrington & Oliver, 1999). The tools and components used for such a variety of purposes include the presentation of information using static visual displays (Mitchell, 2000), animations with audio (Hartley, 2000), multimedia modules, e-mail, listserves and chat rooms.…”
Section: Use Of a Web Environmentmentioning
confidence: 99%
“…Design of web-based instruction requires careful analysis of the available resources of the web for delivering the information in conformity with instructional design principles. Bannan-Ritland et al (1998) propose a hierarchical framework as shown in Table 1, for web-based instruction delivery. Figure 1 gives a rough model of the factors influencing the process of learning and teaching (Gorny, 1997;Meyer, 1991).…”
Section: Design Backgroundmentioning
confidence: 99%